Fenomena Meningkatnya Angka Pernikahan Dini Pada Masa Pandemi COVID-19 di Kecamatan Ngrayun Kabupaten Ponorogo - Pricahyono, Moh Rizal; Arjawa, I Gusti Putu Bagus Suka; Tamim, Imron Hadi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study focuses on the phenomenon of increasing rates of early marriage in Ngrayun District, Ponorogo Regency. The aim of this research is to explain and analyze the increasing number of early marriages occurring in Ngrayun sub-district, Ponorogo Regency. The method used in this research is a qualitative approach with a descriptive-explanatory type. The theory chosen as a scalpel in analyzing this research is Max Weber's theory of social action. The results of this research reveal that the phenomenon of increasing rates of early marriage that occurred in Ngrayun sub-district, Ponorogo Regency during the COVID-19 pandemic experienced a quite drastic increase. This is based on several causes including 1) Law Number 16 of 2019 as an amendment to Law Number 1 of 1974, 2) the relationship between parents' economic conditions and interest in pursuing education, 3) promiscuity among teenagers and dating relationships. which has been established for a long time, 4) Environment. Meanwhile, the impact on social life is 1) Increasing the number of school dropouts, 2) Lack of emotional maturity which leads to divorce, 4) The rise of unregistered marriages in society and 5) The occurrence of domestic violence..